Positive body image is positively associated with hedonic (emotional) and eudaimonic (psychological and social) well-being in British adults. Issue 5 (3rd September 2018) - Swami, Viren; Weis, Laura; Barron, David; Furnham, Adrian
ABSTRACT: Studies examining associations between positive body image and well-being have used a limited array of measures of each construct. To rectify this, we asked an online sample of 1148 U.K. adults to complete a range of measures of positive body image (body appreciation, body image flexibility, body pride, body acceptance from others) and a multi-dimensional measure of well-being (emotional, psychological, and social). Results showed that, once the effects of age and body mass index (BMI) had been accounted for, body appreciation significantly predicted all dimensions of well-being. Other positive body image measures emerged as significant predictors, but patterns of associations were mixed across sex and well-being dimension. Additional analyses showed that women had significantly lower scores than men on most body image measures, and that BMI was negatively associated with all body image measures. These results have implications for the promotion of well-being, which we discuss.